Inventory accounting analysis at pt. Andalas independent son of Pekanbaru - Darmi Darmi (Indonesia Accounting Research Journal, 2023)
PT. Andalas Putra Mandiri is a trading company engaged in the sale of medicines and medical devices, which is located at Jalan Thamrin No.124, Sukamaju sub-district, Sail sub-district, Pekanbaru City. For companies, inventory is the largest item in the financial statements and absorbs very large investments. This makes the writer feel the need to conduct research based on Financial Accounting Standards No. 14 relating to the presentation of inventory estimates in the financial statements, with the title "Inventory Accounting Analysis at PT. Andalas Putra Mandiri Pekanbaru”. The purpose of this research is to find out how PT. Andalas Putra Mandiri Pekanbaru determines the cost of inventory, evaluates inventory and presents inventory in the financial statements. The method used in this research is descriptive method, while the data collection method used consists of interviews and documentation. From this study, the authors found several deviations including errors in determining the cost of inventory and presenting inventory estimates in the financial statements. The author draws the conclusion that inventory accounting at PT. Andalas Putra Mandiri Pekanbaru has not been implemented in accordance with what is regulated in the Financial Accounting Standards. The company should apply inventory accounting in accordance with the applicable Financial Accounting Standards.